1997
DOI: 10.1073/pnas.94.23.12539
|View full text |Cite
|
Sign up to set email alerts
|

ER-27319, an acridone-related compound, inhibits release of antigen-induced allergic mediators from mast cells by selective inhibition of Fcɛ receptor I-mediated activation of Syk

Abstract: Engagement of the mast cell high-affinity receptor for immunoglobulin E (IgE) Allergen-induced activation of the high-affinity receptor for IgE (FcRI) in mast cells and basophils plays a pivotal role in the initiation of allergic and inflammatory reactions. As a result of receptor engagement, mast cells and basophils release a variety of inflammatory mediators, such as histamine, arachidonic acid metabolites, and cytokines (1, 2). The activation of protein tyrosine kinases (PTKs) is one of the early and critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…This is consistent with prior studies on the localization of tyrosine phosphorylated PKC-d (Li et al, 1994b;Haleem-Smith et al, 1995;Solto and Toker, 1995;Denning et al, 1996). Furthermore, we found that the Syk-selective inhibitors, piceatannol and ER-27319, had neither an eect on the tyrosine phosphorylation of PKC-d nor on the activity of Lyn (data not shown and Moriya et al, 1997). Collectively the results exclude mast cell tyrosine kinases, like Syk and Bruton's tyrosine kinase (BTK, Kawakami et al, 1996), that are recruited to the membrane in response to FceRI engagement.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with prior studies on the localization of tyrosine phosphorylated PKC-d (Li et al, 1994b;Haleem-Smith et al, 1995;Solto and Toker, 1995;Denning et al, 1996). Furthermore, we found that the Syk-selective inhibitors, piceatannol and ER-27319, had neither an eect on the tyrosine phosphorylation of PKC-d nor on the activity of Lyn (data not shown and Moriya et al, 1997). Collectively the results exclude mast cell tyrosine kinases, like Syk and Bruton's tyrosine kinase (BTK, Kawakami et al, 1996), that are recruited to the membrane in response to FceRI engagement.…”
Section: Discussionsupporting
confidence: 82%
“…Rather, Ag-stimulated basophils release mediators that induce both acute and late phase allergic responses; they are major sources of IL-4 and IL-13, key cytokines in the propagation of allergic inflammation, and there is a strong relationship between clinical improvement induced by anti-IgE immunotherapy and reduced Fc⑀RI-mediated basophil degranulation (17,26,27). In rodent models, all methods to eliminate Syk, use of Syk-selective inhibitors (28,29), of Syk-negative cell lines (30), of cells from Syk knockout mice (31), and by use of Syk antisense oligonucleotides (32) have consistently eliminated most or all Fc⑀RI signaling responses. However, human allergy is unlikely to be easily treated with Syk inhibitors because this kinase is essential for many other functions, including the development and function of T cells, B cells, and platelets (20,33).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether these pathways were also involved in IL-10 production after contact between BCG-infected DCs and neutrophils. Treatment of BCG-DC-neutrophil cocultures with the two Syk inhibitors, piceatannol and ER27319 (39,40), substantially reduced IL-10 secretion (Fig. 3A).…”
Section: Dcs Infected With Live Bcg Instruct Neutrophils To Produce Imentioning
confidence: 99%